Mapping Transcriptome Data to Protein–Protein Interaction Networks of Inflammatory Bowel Diseases Reveals Disease-Specific Subnetworks - Maden, Sefika Feyza; Acuner, Saliha Ece (Frontiers in Genetics, 2021)
Inflammatory bowel disease (IBD) is the common name for chronic disorders associated with the inflammation of the gastrointestinal tract. IBD is triggered by environmental factors in genetically susceptible individuals and has a significant number of incidences worldwide. Crohn's disease (CD) and ulcerative colitis (UC) are the two distinct types of IBD. While involvement in ulcerative colitis is limited to the colon, Crohn's disease may involve the whole gastrointestinal tract. Although these two disorders differ in macroscopic inflammation patterns, they share various molecular pathogenesis yet the diagnosis can remain unclear and it is important to reveal the molecular signatures of them in the network level. Improved molecular understanding may reveal disease type-specific and even individual-specific targets. To this aim, we determine the subnetworks specific to UC and CD by mapping transcriptome data to protein-protein interaction (PPI) networks using two different approaches (KeyPathwayMiner (KPM) and stringApp) and perform the functional enrichment analysis of the resulting disease type-specific subnetworks. TP63 was identified as the hub gene in the UC-specific subnet and p63 tumor protein, being in the same family as p53 and p73, has been studied in literature for the risk associated with colorectal cancer and IBD. APP was identified as the hub gene in the CD-specific subnet and it has an important role in the pathogenesis of Alzheimer's disease (AD). This relation suggests that some similar genetic factors may be effective in both AD and CD. Lastly, in order to understand the biological meaning of these disease-specific subnets, they were functionally enriched. It is important to note that, chemokines – special types of cytokines – and antibacterial response are important in UC-specific subnets; whereas cytokines and antimicrobial responses as well as cancer-related pathways are important in CD-specific subnets. Overall, these findings reveal the differences between IBD subtypes at the molecular level and can facilitate diagnosis for UC and CD as well as provide potential molecular targets that are specific to disease subtypes.